Family Attitudes and Communication about Sun Protection and Sun Protection Practices among Young Adult Melanoma Survivors and Their Family Members. Issue 11 (2nd November 2021) - Manne, Sharon; Kashy, Deborah A.; Pagoto, Sherry; Peterson, Susan K.; Heckman, Carolyn J.; Gallo, Joseph; Berger, Adam; Buller, David B.; Kulik, Alexandria; Frederick, Sara; Pesanelli, Morgan
ABSTRACT: Young melanoma survivors and their family are at increased risk for developing melanoma, but seldom engage in sun protection behaviors. Little is known about the role of family factors in sun protection. Our goals were: 1) examine correspondence between survivors and family sun protection, individual attitudes, and family attitudes and communication about risk-reducing behaviors, and; 2) evaluate the mediating role of family attitudes and communication in the association between individual sun protection attitudes and behavior. Measures of individual attitudes, family attitudes and communication, and sun protection behaviors were completed by 529 participants. Multilevel modeling assessed family correspondence in sun-related attitudes and behaviors and mediation. Families had varying levels of shared attitudes and behaviors, with higher correspondence for family norms. Survivors reported stronger family norms, greater family benefits, and more discussion than siblings. For both sexes, family discussion was associated with higher sun protection. For women only, more favorable attitudes were associated with sun protection partly because women discussed sun protection with family and held stronger norms. Because families' attitudes and practices correspond, family-focused interventions may prove effective. Among females, increasing risk awareness and sunscreen efficacy and overcoming barriers may foster enhanced normative standards, communication about, and engagement in sun protection.